2006
DOI: 10.1007/s00439-006-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of SOD2 variants with methamphetamine psychosis in Japanese and Taiwanese populations

Abstract: SOD2 (superoxide dismutase 2) plays a crucial role in protecting the cells against damage caused by free radicals, by catalyzing their detoxification. On the other hand, cell damage caused by free radical generation following methamphetamine administration has been postulated as one of the possible pathophysiological mechanisms for methamphetamine psychosis. Hence, we investigated the association of SOD2 polymorphisms with the development of methamphetamine psychosis, in two independent populations of Japan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…These results are in agreement with other studies on white populations, where the Ala/Val genotype predominates (20,24). In contrast, in Asian populations the Val/Val genotype is the most frequent (80%), the Ala/Ala representing less than 5% (25). We found that the Ala/Ala SOD2 genotype significantly influences the pregnancy outcome in IVF.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with other studies on white populations, where the Ala/Val genotype predominates (20,24). In contrast, in Asian populations the Val/Val genotype is the most frequent (80%), the Ala/Ala representing less than 5% (25). We found that the Ala/Ala SOD2 genotype significantly influences the pregnancy outcome in IVF.…”
Section: Discussionsupporting
confidence: 92%
“…The study sample size had at least 80% power (two-sided test significant, α of 0.05) to detect an OR of at least 2.5, following the calculations used in previous studies [9,14,16,2527]. The distribution of each genetic variant in the cases and controls was first assessed for consistency with the Hardy-Weinberg equilibrium (HWE) on a contingency table of observed-versus-predicted genotype frequencies by using Chi-Square Goodness of Fit test.…”
Section: Methodsmentioning
confidence: 99%
“…These studies mostly focus on methamphetamine abuse-related phenotypes. These genes include CES1 (Nemoda et al 2009); DTNBP1 (Kishimoto et al 2008a); FZD3 (Kishimoto et al 2008b); G72 (Kotaka et al 2009); GABRG2 (Nishiyama et al 2005); GLYT1 (Morita et al 2008); GRM2 (Tsunoka et al 2010); GSTM1 (Nakatome et al 2009); GSTP1 (Hashimoto et al 2004); GSTT1 (Nakatome et al 2009); NQO2 (Ohgake et al 2005); PDYN (Nomura et al 2006); PICK1 (Matsuzawa et al 2007); PROKR2 (Kishi et al 2010); SLC22A3 (Aoyama et al 2006); SNCA (Kobayashi et al 2004) and SOD2 (Nakamura et al 2006). …”
Section: Exploratory Studiesmentioning
confidence: 99%